THE MONETARY INDICATORS AND THE CONSUMPTION IN INDONESIA - Ramadhan, Ahmad; Rangkuty, Dewi Mahrani; Suhendi, Suhendi; Efendi, Bakhtiar; Nasution, Lia Nazliana (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Analysis of interest rates, and money supply through Inflation to total consumption in Indonesia is the purpose of this study using the path analysis method. Based on the results showed that interest rates have a direct and significant effect on Inflation. Money supply directly has no significant effect on inflation. Interest rates directly have no significant effect on consumption. Money supply directly has a significant effect on consumption. Inflation directly has no significant effect on consumption. Interest rates, and money supply through inflation have no significant effect on consumption. Bank Indonesia needs to continue to maintain interest rates and money supply which will affect inflation in the market and then affect people's consumption patterns.